Biotic integrity of the Chiquito River subwatershed, Morelia, Michoacán México, based on the aquatic macroinvertebrate assemblages - Piñón Flores, Miguel Aurelio (2014)
The Chiquito River subwatershed supplies 30% of the potable water consumed by the city of Morelia, Michoacan, Mexico. It is necessary to constantly monitor its waters using metrics that evaluate environmental degradation and aquatic assemblages. In the present study, we used the Index of Biotic Integrity for Aquatic Macroinvertebrate Associations (IBIAMA), the Visual-Based Habitat Assessment, and the Most Probable State to calculate the conservation status of the river at six sites along the main channel, including an upper site as a reference. A total of 51 474 specimens were identified, the taxonomic composition was comprised of 69 families distributed into four Phyla, eight classes, eight sub-classes, and 18 orders. The best preserved sites were found in the subwatershed headwater zone. The intermediate zone had impacted hydraulic conditions, environmental quality and biotic integrity. The downstream part of the subwatershed showed the resilient capacity of the river to reestablish macroinvertebrate assemblages and environmental parameters. There is a strong correlation among environmental qualities and the IIBAMA. The use of macroinvertebrates in combination with environmental parameters showed that the Chiquito River subwatershed is stable, rich and integral in aquatic macroinvertebrate assemblages before entering the city of Morelia, and it conserves the processes that regulate the functional dynamics of the subwatershed. Rev. Biol. Trop. 62 (Suppl. 2): 221-231. Epub 2014 April 01.